Current Pharmacologic Approaches for Prevention and Treatment of Bronchopulmonary Dysplasia - Kristen Tropea; Helen Christou (Hindawi Limited, 2012)
Bronchopulmonary dysplasia (BPD) is a major complication of preterm birth and has serious adverse long-term health consequences. The etiology of BPD is complex, multifactorial, and incompletely understood. Contributing factors include ventilator-induced lung injury, exposure to toxic oxygen levels, and infection. Several preventive and therapeutic strategies have been developed with variable success. These include lung protective ventilator strategies and pharmacological and nutritional interventions. These strategies target different components and stages of the disease process and they are commonly used in combination. The purpose of this review is to discuss the evidence for current pharmacological interventions and identify future therapeutic modalities that appear promising in the prevention and management of BPD. Continued improved understanding of BPD pathogenesis leads to opportunities for newer preventive approaches. These will need to be evaluated in the setting of current clinical practice in order to assess their efficacy.